Effect of exercise on depression in elderly - Hekmati Pour N; Hojjati H; Sharif Nia H; Akhondzade G; Nikjou AR; Mir Abolhasani M (آموزش بهداشت و ارتقاء سلامت ایران, 2013)
Background and objective: Along with with aging problems among nations and depression as the most common mental disorder in the elderly has been growing and becoming aglobal problem of human life as a central concern in the health of the elderly. The purpose of this study to determine the impact of exercises on depression among older people. Method: In this experimental study, 48 elderly people attending day centers for the elderly were randomly selected divided into test and control groups. This study design was based on Solomon proposals. Groups had 4 weeks of regular exercises during the 16 sessions of 15- 25 minutes and control group had routine activities performed in the center. Both groups completed questionnaires assessing demographic information and depression using Beck Depression Inventory (BDI). Descriptive statistics and inferential statistics (two-way ANOVA) were used to analyze the data. Results: Controlling for the impact of pre-test results of two-way ANOVA revealed significant difference between intervention and control groups in depression scores (p‹0.001) of seniors exercise program. Conclusion: This study showed regular exercise is effective in reducing depression among the elderly. Thus it is expected that regular exercises be used as a complementary effective measure with other current treatments and low complications as a non-drug treatment of depression.